Drop jump and muscle damage markers - Eiras, A. E.; dos Reis, R. L.; Silva, P. A.; Monteiro, A. N.; Pereira, R.; Machado, M. (Serbian Journal of Sports Sciences, 2009)
Plyometric exercises use rapid, powerful movements preceded by a preloading countermovement that activates the Stretch-Shortening Cycle (SSC). The Drop Jump (DJ) is a very common SSC exercise used in sport training which is eccentric-biased. Eccentric actions are associated with skeletal muscle tissue damage, and serum muscle enzyme activity like CK and LDH are used as muscle damage markers. The aim of this study was to measure the magnitude of muscle damage markers after a DJ session. Sixteen men (18±3 years old; 177± 4 cm height; and 71±4 kg weight) were submitted to 4 sets of 10 Drop Jumps from 30 cm with 1 min interval between the series. All had blood collected before and after the exercise (24, 48 and 72h) to assay the serum activity of CK and LDH. One-way analysis of variance (ANOVA) was used to test the differences in serum enzyme activity and the alpha level was set at 0.05. The serum CK activity increased significantly in all samples, reaching the peak at 72 h after exercise (~ 277%; p<0.01). A similar result was reached with the activity of serum LDH (~ 100% increase at 72h; p<0.05). None of the results exceeded the reference values proposed for athletes. We have concluded that the DJ causes changes in muscle metabolism indicators increasing serum CK and LDH activity.